Konstruksi Stunting Masyarakat Perkotaan: Proses Eksternalisasi, Objektivasi, Dan Internalisasi - Ma'krufi, Jamiatul; Nurbayani, Siti; Wahyuni, Sri (University of Jember, 2024)
Quality human resources are one of the factors that influence a nation's ability to develop physically and mentally. Because many children under five who experience stunting are caused by the environment or parenting. The incidence of stunting in Kebonwaru RW 03 Village with a total of 22 stunted toddlers aged 0-24 months. This study aims to examine how the social construction of the Kebonwaru community in efforts to prevent stunting in toddlers. The approach used in this research is qualitative with descriptive method research. The results of this study indicate that stunting generally occurs in children under five, especially those aged between 6 months and 5 years. Newborn children and toddlers aged 6 months and above need a lot of nutrients to support better growth. If one of the nutrients provided is less than needed, the child will suffer from stunting.